2016
DOI: 10.1530/erc-15-0555
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced thyroid cancer with targeted therapies: ten years of experience

Abstract: Thyroid cancer is rare, but it is the most frequent endocrine malignancy. Its prognosis is generally favorable, especially in cases of well-differentiated thyroid cancers (DTCs), such as papillary and follicular cancers, which have survival rates of approximately 95% at 40 years. However, 15-20% of cases became radioiodine refractory (RAI-R), and until now, no other treatments have been effective. The same problems are found in cases of poorly differentiated (PDTC) and anaplastic (ATC) thyroid cancers and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
130
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 134 publications
(134 reference statements)
0
130
0
1
Order By: Relevance
“…In the past 10 years, many TKI have been evaluated, including RET-blocking compounds (Plaza-Menacho et al 2014, Viola et al 2016. Based upon the preclinical data on MTC cell cultures, various clinical trials have been conducted that confirmed the efficacy of RET-targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, many TKI have been evaluated, including RET-blocking compounds (Plaza-Menacho et al 2014, Viola et al 2016. Based upon the preclinical data on MTC cell cultures, various clinical trials have been conducted that confirmed the efficacy of RET-targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several tyrosine kinase inhibitors (axitinib, cabozantinib, gefitinib, imatinib, motesanib, sorafenib, sunitinib and vandetanib) have been evaluated in phase I, II and III clinical trials of patients with advanced MTC. These drugs increased progression-free survival, however, with time, the MTC becomes resistant to these drugs and the disease progresses , Viola et al 2016. In addition, few preliminary clinical studies evaluated the potential beneficial effects of mTOR inhibitors in the treatment of MTC, showing the stabilisation of disease in most of patients treated with everolimus (Druce et al 2012, Faggiano et al 2012, Lim et al 2013, Schneider et al 2015.…”
Section: :1mentioning
confidence: 99%
“…Thyroid cancer is the most common type of endocrine malignancy (1). According to the World Health Organization, thyroid cancer may be classified into four subtypes based on its histopathological characteristics: Papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC), medullary thyroid carcinoma (MTC) and anaplastic thyroid carcinoma (ATC) (2).…”
Section: Introductionmentioning
confidence: 99%